Cancer Is to Embryology as Mutation Is to Genetics: Hypothesis of the Cancer as Embryological Phenomenon - Jaime Cofre; Eliana Abdelhay (The Scientific World Journal)
Despite numerous advances in cell biology, genetics, and developmental biology, cancer origin has been attributed to genetic mechanisms primarily involving mutations. Embryologists have expressed timidly cancer embryological origin with little success in leveraging the discussion that cancer could involve a set of conventional cellular processes used to build the embryo during morphogenesis. Thus, this “cancer process” allows the harmonious and coherent construction of the embryo structural base, and its implementation as the embryonic process involves joint regulation of differentiation, proliferation, cell invasion, and migration, enabling the human being recreation of every generation. On the other hand, “cancer disease” is the representation of an abnormal state of the cell that might happen in the stem cells of an adult person, in which the mechanism for joint gene regulating of differentiation, proliferation, cell invasion, and migration could be reactivated in an entirely inappropriate context.